Predicting Financial Distress and Bankruptcy of PT Sepatu Bata Tbk with Six Methods - Sucipto, Rakhmat Hadi; Sumantri, Fazhar; Taruna, Helmy Ivan (Jurnal Economic Resource, 2024)
This study aims to estimate the financial difficulties that may be experienced by PT Sepatu Bata Tbk, compare six bankruptcy prediction methods, namely Altman, Springate, Zmijewski, Grover, Ohlson, and Taffler, and find the accuracy level of the predictive model. The research uses a quantitative approach by utilizing an independent sample t-test to detect comparisons between bankruptcy prediction methods from the company's secondary data. The results of the study show that the Altman method successfully detected the existence of financial distress of the company, namely in 2020, 2022, and 2023, while the rest of the time the company was still safe and entered the gray area, the Springate method predicts that for 12 years from 2012 to 2023 the company was trapped in the threat of bankruptcy due to financial distress, the Grover method found the fact that throughout the year from 2012 to 2023 the company experienced financial difficulties, Zmijewski's method proves that companies are experiencing financial distress only in 2023, Ohlson's method detects that companies are still in good health for 12 years from 2012 to 2023, and the Taffler model predicts that companies have experienced various conditions over the past 12 years and are only threatened with bankruptcy in 2020 and 2021. The Taffler method showed the highest accuracy rate of 83%, followed by the Altman and Zmijewski methods at 75%, Ohlson at 65%, and Springate and Grover both recorded an accuracy rate of 33%.